2004
DOI: 10.1023/b:phot.0000040578.93542.61
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effects of Salinity and Ozone Pollution on Photosynthesis, Stomatal Conductance, Growth, and Assimilate Partitioning of Wheat (Triticum aestivum L.)

Abstract: Plants of an Egyptian cultivar of wheat (Triticum aestivum L. cv. Giza 63) were exposed in open-top chambers (OTCs) for 8 h d -1 for up to 75 d to a factorial combination of two levels of salinity (0 and 50 mM NaCl) and two levels of O 3 (filtered air and 50 mm 3 m -3 ). Exposure to 50 mm 3 m -3 O 3 significantly decreased stomatal conductance (g s ), net photosynthetic rate (P N ), and chlorophyll (Chl) content by 20, 25, and 21 %, respectively. This reduction resulted in a change in assimilate allocation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 35 publications
(46 reference statements)
3
12
1
Order By: Relevance
“…1b) is in line with earlier publications, reporting in particular increases in the number of inflorescences in both C. angustifolium and B. inermis near the Bratsk aluminium smelter (Lyubashevskii et al 1996), and in the number of generative shoots in Taraxacum officinale Weber ex Wiggers near the metallurgical plant in Nizhny Tagil (Zhuikova et al 2002). Intensification of reproduction with increase in pollution was earlier reported for willows and dwarf shrubs in surroundings of the Monchegorsk smelter (Zvereva and Kozlov 2001, 2004, 2005 and in a herb Potentilla anserina L. under experimental increase of heavy metals (Saikkonen et al 1998). These results suggest existence of pollution tolerance in plant populations growing in polluted sites, because the stress-resistant populations are expected to have higher reproductive output under stressful conditions (Hoffmann and Parsons 1991).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…1b) is in line with earlier publications, reporting in particular increases in the number of inflorescences in both C. angustifolium and B. inermis near the Bratsk aluminium smelter (Lyubashevskii et al 1996), and in the number of generative shoots in Taraxacum officinale Weber ex Wiggers near the metallurgical plant in Nizhny Tagil (Zhuikova et al 2002). Intensification of reproduction with increase in pollution was earlier reported for willows and dwarf shrubs in surroundings of the Monchegorsk smelter (Zvereva and Kozlov 2001, 2004, 2005 and in a herb Potentilla anserina L. under experimental increase of heavy metals (Saikkonen et al 1998). These results suggest existence of pollution tolerance in plant populations growing in polluted sites, because the stress-resistant populations are expected to have higher reproductive output under stressful conditions (Hoffmann and Parsons 1991).…”
Section: Discussionsupporting
confidence: 54%
“…Many of these studies -conducted both in fully controlled environment and under field conditions -reported adverse effects of different pollutants on growth of herbaceous plants (e.g. Brun et al 2003;Tuma 2003;Hassan 2004;Rämö et al 2006;Ryser and Sauder 2006). Consistently, many ecotoxicological tests are based on measurements of size or biomass of herbaceous plants (Rajput and Agrawal 2005;An 2006;Everhart et al 2006;Rombke et al 2006;Rooney et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Salt tolerant cultivars access selective uptake of K + at cellular level (Erdei et al 1991). These effects interact in wheat with other abiotic effects such as O 3 (Hassan 2004). Pier and Berkovitz (1987) found that raising intracellular K + content reversed the inhibition of photosynthesis in osmotically stressed wheat leaves.…”
Section: --mentioning
confidence: 99%
“…Under natural conditions, environmental factors contributing to photosynthetic response function in complex and vary simultaneously and these anticipate intricacy (Jones 1992, Kobayashi et al 1999, Deng et al 2000, Hassan 2004). Kassim and Paulsen (1999) indicated that wheat plants had higher P N at 22 o C than when exposed to 45 o C, whereas leaf P N of rice increased at 22 o C and decreased at 42 o C.…”
mentioning
confidence: 99%